Association between high-sensitivity C-reactive protein and lipid profile in patients with type 2 diabetes mellitus - Muniyal, Himani; Jheetay, Sanket; Mishra, Arun (International journal of health sciences, 2022)
Background: The most significant and challenging health issue of the modern era is diabetes mellitus and its complications. Inflammation plays a crucial role in the development and progression of diabetes. Type 2 Diabetes Mellitus patients(T2DM) are at significant risk of developing cardiovascular diseases. High-sensitive CRP (hs-CRP) has become a reliable indicator of low-grade inflammation. Since very little is known regarding the relationship between hs-CRP and T2DM, the goal of this study was to evaluate hs-CRP levels and lipid profile and to study their relationship to cardiovascular problems in Type 2 Diabetes Mellitus patients. Material and Methods: The current study was carried out at Index Medical College and Hospital in Indore. The study group consisted of 70 healthy controls and 70 Type 2 Diabetes Mellitus patients who had been diagnosed following WHO criteria. Serum hs-CRP concentrations as well as the lipid profile (total cholesterol, HDL, and TG) were assessed. SPSS version 26 was used to analyze the data. Results: In comparison to controls, individuals with Type 2 Diabetes Mellitus had significantly higher levels of hs-CRP, with a mean value of 2.49 + 1.15 mg/L (p <0.001).